Identifying aquaculture potential in northern Ghana: assessing small reservoirs using surface area dynamics, hydrological regimes, and socio-economic indicators - Akpoti, Komlavi; Zwart, Sander J.; Buisson, Marie-Charlotte (International Water Management Institute, 2024)
This study presents a comprehensive assessment of small reservoir suitability for aquaculture development in Northern Ghana, focusing on approximately 2000 small reservoirs. By mapping surface area dynamics during the dry season (November to April) from 2018 to 2024, we identified significant variations in water availability. Among these reservoirs, 450 were surveyed to gather detailed information on multiple uses, including irrigation and aquaculture. To enhance our understanding, we organized a workshop to gather expert opinions on critical biophysical and socio-economic indicators for aquaculture development. Using this expert input, coupled with the survey data and surface area dynamics, we evaluated the potential of each reservoir for aquaculture. Additionally, we assessed discharge variability and its contribution to water availability in the reservoirs using the VegDischarge v2 data for the upstream catchment of each reservoir. Our findings highlight the reservoirs most suitable for aquaculture, providing a robust framework for sustainable aquaculture development in the region. This analysis supports water resource management and promotes resilient aquatic food systems, addressing food security and economic development in Northern Ghana.